Physical activity level and health risk behavior of Physical Education students (Research, Society and Development, 2020)
This study aims to verify the level of physical activity and health risk behaviors of students of the Physical Education course of a public university in the interior of Rio Grande do Sul, Brazil, from a descriptive exploratory study of a quantitative character. The International IPAQ questionnaire was used to assess the level of physical activity and the Global School-based Student Health Survey questionnaire for health risk behaviors. It was found that 75% of students perform physical activities beneficial to health with intensity and duration. Among the variables, there was a significant association between the consumption of drink alcohol and tobacco consumption (p = 0.009), between self-perceived health and consumption of drink alcohol (p = 0.019) and smoking consumption (p = 0.025), one positive linear trend between the use of illicit drugs and the semester attended (p = 0.048) and, a negative linear trend between the semester attended and the consumption of fruits/vegetables (p = 0.043). It was concluded that most of those surveyed perform physical activities habitually, but maintain an inadequate diet, drink alcohol, use tobacco and, a small percentage, use illicit drugs frequently. Despite having health risk behavior, they are aware of the harmful effects of these behaviors.